A importância da pesquisa de egresso para tomada de decisão e como suporte para políticas de assistência, permanência e êxito no ensino médio integrado do Campus Irecê do Instituto Federal da Bahia - Barreto, Júlio Cézar Araújo (2022)
The purpose of this work is to know the profile of the graduates of the Campus Irecê of the Instituto Federal da Bahia and to propose the reinsertion of this participant in the institution in order to support and support the activities and actions of the campus. Success in the teaching and learning process lies in the sum of efforts of professionals working in education, committed students and continuous monitoring of educational processes and results, through research and feedback. In this process, student assistance programs are extremely relevant and help students in the training process. The graduate has a fundamental role, as he is the protagonist and culmination of the teaching and learning process, which carries with him the experiences, difficulties and challenges faced during the training cycle and which ends up becoming a potential source of information and suggestions that may assist in decision making and in the improvement and enhancement of the teaching and learning process of an educational institution. In addition, one of the proposals of Vocational and Technological Education is that the student understands work as an educational principle, without a social or technical division, without a segregation between humanistic knowledge and specific knowledge of professional education, which is possible through a polytechnic training. and omnilateral of the participant. In this context, the present work aimed to carry out an action research on the importance of graduate research as a parameter of institutional analysis and evaluation, comprising management, sectors linked to teaching, the graduate's view of teaching practice, the world of work and the student assistance actions in the determination of permanence and success policies in the Integrated High School of the Irecê Campus of the Federal Institute of Bahia. The work used a literature review, document analysis and data collection through interviews and questionnaires. With a quali-quanti approach, the research made use of dialectics in conversation circles and virtual chats with graduates. At the culmination of the work, as an educational product proposal, the “Egress Portal” was created, a portal for the integration, interaction and participation of the egress in the activities and actions of Campus Irecê. The portal will have free access for research and user registration for editing and permanent collaborations. It is believed that the educational product can significantly contribute to the monitoring of graduates, maintaining a two-way affective and contributory bond, culminating in positive results in the short term and becoming a practical management tool, thinking in the medium and long term.